Auditoría Financiera al Gobierno Autónomo Descentralizado Parroquial Rural de Chuquiribamba del Cantón Loja, Periodo 2021. - Cuenca Merchán, Jhomara Briggette (2023)
The Financial Audit of the Decentralized Autonomous Rural Parochial Government of Chuquiribamba of Loja Canton, period 2021, was conducted with the purpose of presenting a contribution to the managers and officials of the institution for proper decision making and timely correction of deficiencies and irregularities detected, through the issuance of a Financial Audit report, containing the auditor's opinion, comments, conclusions and recommendations. Likewise, to demonstrate the reasonableness of the balances presented in the Financial Statements and to determine whether the institution maintains adequate internal control in accordance with current legal regulations. With the application of the appropriate methodology, both the general and specific objectives were met. The first specific objective was fully executed, since, in order to develop the work, we began with the evaluation of the internal control system, which turned out to be deficient, due to the fact that, bank reconciliations are not performed monthly, which prevents knowing the real balance of the Banco Central del Ecuador Legal Currency account, no surprise audits are performed, no daily reports are made of the amounts collected in cash, there is no adequate segregation of duties, periodic physical checks are not performed, there is no timely disposal of assets, there is no custodian, there are no maintenance programs for long-lived assets, the maturity of payments is not controlled, there is no periodic analysis of the aging of accounts payable, there are no daily verifications of revenues, transfers are not accounted for in a timely manner and a chronological file is not kept of the roles of payment cancelled to employees, this is due to the non-observance of certain internal control standards, which has caused the balance presented in the financial statements to be unreliable. The second objective was carried out during the course of the audit, since substantive and compliance tests were applied to demonstrate that the financial statements do not contain errors or irregularities. Finally, the last objective was fulfilled with the presentation of the financial audit report and it was concluded that the balances presented in the financial statements are not true and therefore the respective adjustments should be made. In addition, there is an inadequate management of property, plant and equipment, which makes it difficult to have proper control of the institution's assets. As a result of the audit, it is proposed to the administration to make the pertinent adjustments to reasonably present the financial information generated in the year 2021 and comply with the recommendations set forth in the audit report and thus avoid problems and inconveniences with subsequent audits